Modelling strain penetration effects in RC walls with smooth steel bars. Issue 17 (5th June 2018) - Caruso, Claudia; Bento, Rita; Sousa, Romain; Correia, António A.
Abstract : Reinforced-concrete (RC) dual wall–frame structures comprise an important proportion of the building stock in some European cities. However, many were constructed without seismic provisions and it is therefore important to assess their ability to withstand seismic events and to define strategies to reduce their potential vulnerability. This work focuses on the numerical simulation of the seismic behaviour of RC walls making use of fibre-based non-linear beam elements. Even though it is common to assume perfect bond between reinforcing bars and concrete, the relative bond–slip deformations between the two materials can contribute up to 40% of the total lateral deformation of columns when ribbed rebars are used and up to 90% in the case of smooth rebars. The aim of this paper is to provide a contribution towards understanding the importance of these effects in old RC walls and to provide indications regarding the use of a simplified bond–slip model.